Studi Reproduksi Induk Udang Vaname (Litopenaeus vannamei) Pada Kolam Pemeliharaan Unit Induk III PT. Esaputlii Prakarsa Utama - Wardha Jalil; Supasman Emu; Fatimah (AquaMarine (Jurnal FPIK UNIDAYAN ), 2022)
The study aims to find out and increase knowledge about the reproduction broodstock of vaname shrimp in PT. Esaputlii Prakarsa Utama. The data analysis methods used are descriptive and quantitative analysis. Vaname shrimp broodstock management techniques activities start from water procurement, tub/pond preparation, broodstock procurement, acclimatization, eye abalation, maturation and maintenance including feed management and water quality, spawning, hatching eggs to harvesting. The results showed that the amount of feeding ranged from 500 grams/tub for squid feed, 1 kg/tub for sea worm feed. Broodstock who are able to spawn have an average of 41-42 /day from an average number of 333 shrimp. The percentage of female vanames that spawn ranges from 84%/day. The number of eggs produced by vaname shrimp reached 100,250–261,923 eggs in one month, the average egg that was fertilized was 9,668,333 and produced naupli as many as 8,955,000. The water quality parameters obtained during the research were still in a good range for vannamei shrimp.